Pengaruh Teknik Jahit Bulu Mata Terhadap Hasil Riasan Mata Sipit Untuk Tata Rias Wajah Pengantin Eropa - Haloho, Glori Anastasya; Susilowati; Fatmasari, Fitria Hansyah (Jurnal Tata Rias, 2025)
This study examines the effect of the eyelash sewing technique on monolid eye makeup results in European bridal styling. A quantitative one-shot case study was employed. Expert panels completed Likert-scale ratings complemented by visual documentation. Results indicate a significant difference between the sewing technique (mean 60.80) and non-sewing (mean 36.70); the paired t-test yielded p = 0.000 (p < 0.05). The technique enhances aesthetics, proportion, and durability, thus recommended for brides with monolid eyes.